Cell surface Thy-1-cross-reactive glycoprotein in cultured PC12 cells: modulation by nerve growth factor and association with the cytoskeleton - Richter-Landsberg, C (J Neurosci, 1985)
In cultured PC12 rat pheochromocytoma cells, nerve growth factor (NGF) selectively stimulated the incorporation of [3H]fucose into a glycoprotein of apparent Mr approximately 25,000, as determined by sodium dodecyl sulfate-gel electrophoresis. Neither dibutyryl cyclic adenosine 3′:5′-monophosphate nor epidermal growth factor mimicked this effect. Using gradient gels, the affected protein was resolved into two closely migrating bands. Enhancement of labeling was present by 1 to 2 days of treatment with NGF and was maximal after 4 to 7 days. Short- term extraction of PC12 cell monolayer cultures with Triton X-100 left the 25,000-dalton glycoprotein associated with the detergent-resistant cytoskeletal fraction. The Mr approximately 25,000 glycoprotein was shown to be immunologically cross-reactive with Thy-1.1 antigen by indirect immunoprecipitation with monoclonal Thy-1.1 antibodies. Anti- Thy-1.1 labeling, as demonstrated by indirect immunofluorescence, was distributed on PC12 cell bodies and along neuritic processes and remained attached to the cytoskeleton as part of the surface lamina of cells treated and untreated with NGF. The selective increase of the Mr approximately equal to 25,000 glycoprotein in NGF-treated cultures was also paralleled by increases in material immunoprecipitated from fucose- labeled cells with anti Thy-1.1 monoclonal antibodies. Immunoprecipitations with extracts of [35S]methionine-labeled cultures indicated that NGF causes an increase in synthesis, rather than merely glycosylation, of the 25,000-dalton/Thy-1-cross-reactive protein. The effect of NGF on this protein was blocked by inhibitors of RNA synthesis, suggesting involvement of a transcription-dependent mechanism.(ABSTRACT TRUNCATED AT 250 WORDS)